Those Bearded Men and Their Beautiful Machines. Remarks on Contemporary Cafe Racer Culture - Drozdowicz, Jarema (Wydawnictwo Naukowe UAM, 2016)
The contemporary phenomenon of the cafe racer culture raises today many questions on the culturally defined identities and the nature of modern subcultures. This paper examines those issues by highlighting both, the most significant elements of the cafe racer subculture and by conceptualizing the cultural reality surrounding these groups of motorized people. As the place of the motorcycle in popular culture links this machine with masculinity a further inquiry is being made her in the construction of the male rider image.
Keywords: cafe racer; scrambler; motorcycle; subculture; identity; popular cultrue; mods; rockers